Titanium / steel composite material microstructure detection and characterization method, system, equipment and medium

Through ultrasonic scanning microscope, the detection parameters are adjusted to obtain B and C scan images of the titanium/steel composite bonding interface, which solves the problem of difficulty in detecting interface wave height and corrugation width in the prior art, and achieves efficient and accurate detection of the microstructure of titanium/steel composite.

CN119827633APending Publication Date: 2025-04-15UNIV OF SCI & TECH BEIJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411315552.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently and accurately detect the microstructure of the bonding interface of titanium/steel composite materials, especially the inability to detect the interface wave height and corrugation width simultaneously.

Method used

Ultrasonic scanning microscope is used to detect the microstructure of titanium/steel composite materials. By adjusting the parameters such as probe frequency, stepping, gain and focus depth, B and C scan images are obtained, and indicators such as wave height and ripple width are obtained through image analysis.

Benefits of technology

It realizes efficient and accurate detection of the titanium/steel composite bonding interface, can obtain detailed microscopic information, and supports material performance evaluation and quality control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119827633A_ABST
    Figure CN119827633A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium / steel composite material microstructure detection and characterization method, system, equipment and medium. According to the method, a plurality of detection parameters of the ultrasonic scanning microscope are collaboratively optimized, so that high-quality B-scanning and C-scanning ultrasonic images are obtained. Wave height and ripple width indexes are selected to represent the microstructure, accurate detection of the microstructure of the titanium / steel composite material bonding interface is achieved, detailed microscopic information of the titanium / steel composite material bonding interface can be efficiently and accurately obtained, and important data support is provided for material performance evaluation and quality control.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The invention relates to the field of ultrasonic microscope nondestructive testing, and in particular to a method, system, equipment and medium for detecting and characterizing the microstructure of a titanium / steel composite material. Background Art

[0002] With the development of modern industrial technology, titanium / steel composite materials are widely used in aerospace, shipbuilding, chemical industry and other fields because they have both the excellent corrosion resistance of titanium and the high strength of steel. Titanium / steel composite materials have unique structural characteristics, and their special feature is that the bonding interface of the material presents a corrugated microstructure. This structure not only enhances the bonding strength of the material, but also improves the corrosion resistance and load-bearing capacity of the overall material. The quality of the bonding interface of titanium / steel composite materials directly affects its overall performance, so it is particularly important to accurately detect the microstructure of its bonding interface.

[0003] Traditional detection methods, such as X-ray detection and optical microscope detection, have certain limitations. Although X-ray detection can provide information about the inside of the material, it is radiation-prone to the user; although optical microscopes have high resolution, their use process is complicated and can easily damage the sample. Therefore, a new method that can efficiently and accurately detect the microstructure of the titanium / steel composite interface is urgently needed.

[0004] Although optical microscopes have high resolution, they can only observe the surface of materials and cannot penetrate into the interior of materials. X-ray detection can provide internal information, but there are radiation risks and the detection effect on some materials is not ideal. However, there is currently a lack of an ultrasonic detection method specifically for titanium / steel composite materials, especially a comprehensive characterization method that can simultaneously detect the interface wave height, corrugation width and microstructure. Summary of the invention

[0005] In order to overcome the problems existing in the prior art, the present invention provides a method, system, equipment and medium for detecting and characterizing the microstructure of a titanium / steel composite material.

[0006] A method for detecting and characterizing the microstructure of a titanium / steel composite material, the method comprising the steps of:

[0007] S1. Move the probe of the ultrasonic scanning microscope to a position just above the center of the titanium / steel composite sample;

[0008] S2. According to the thickness of the sample, setting the detection parameters of the ultrasonic scanning microscope;

[0009] S3. The ultrasonic scanning microscope scans and detects the sample to obtain an image of the sample;

[0010] S4. Analyze the image, obtain indicators about the sample, and characterize the sample.

[0011] According to the above aspects and any possible implementation, an implementation is further provided, wherein the titanium / steel composite material sample comprises a titanium layer of the titanium / steel composite material, a steel layer of the titanium / steel composite material, and a titanium / steel composite material bonding interface ripple located therebetween.

[0012] According to the above aspects and any possible implementation, there is further provided an implementation, wherein the thickness of the sample is 10 mm.

[0013] According to the above aspects and any possible implementation manner, there is further provided an implementation manner, wherein the detection parameters include probe frequency, step, gain and focus depth.

[0014] According to the above aspects and any possible implementation, an implementation is further provided, wherein the probe frequency is 50 MHz, the step is 10 μm, the gain is 20 dB, and the focus depth is 2 mm.

[0015] According to the above aspects and any possible implementation manner, an implementation manner is further provided, wherein the image includes a two-dimensional cross-sectional image and a two-dimensional plane image.

[0016] According to the aspects and any possible implementations described above, an implementation is further provided, wherein the two-dimensional cross-sectional XOZ image is used to measure the corrugation height of the sample, and the two-dimensional plane XOY image is used to measure the corrugation width of the sample.

[0017] The present invention also provides a titanium / steel composite material microstructure detection and characterization system, the system is used to implement the method described, the system comprises:

[0018] A positioning module, used for positioning the probe of the ultrasonic scanning microscope and the position of the titanium / steel composite material sample;

[0019] A setting module, used for setting the detection parameters of the ultrasonic scanning microscope according to the thickness of the sample;

[0020] An acquisition module, used for the ultrasonic scanning microscope to scan and detect the sample to obtain an image of the sample;

[0021] The analysis and characterization module is used to analyze the image to obtain an index characterization of the sample.

[0022] The present invention further provides a computer device, which includes a processor and a memory, wherein a computer program is stored in the memory, and the computer program is loaded and executed by the processor to implement the method described in the present invention.

[0023] The present invention also provides a computer-readable storage medium, in which a computer program is stored. The computer program is loaded and executed by a processor to implement the method described above.

[0024] Beneficial effects of the present invention

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention provides a method for detecting and characterizing the microstructure of titanium / steel composite materials. This method realizes accurate detection of the microstructure of titanium / steel composite materials through multi-parameter collaborative detection, including optimization and adjustment of probe frequency, step, gain and focus depth parameters, and can efficiently and accurately obtain detailed microscopic information of titanium / steel composite materials, and extract key features such as wave height and corrugation width from scanning images in different directions, thereby providing important data support for performance evaluation and quality control of titanium / steel composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is the scanning trajectory of the ultrasonic probe and the B-scan and C-scan imaging cross-sectional diagram in the present invention;

[0028] Figure 2 It is a schematic diagram of the bonding interface of the titanium / steel composite material in the present invention;

[0029] Figure 3 It is a B-scan image of the bonding interface of the titanium / steel composite material in the present invention;

[0030] Figure 4 It is a C-scan image of the bonding interface of the titanium / steel composite material in the present invention. DETAILED DESCRIPTION

[0031] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0032] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0034] The bonding interface of titanium / steel composite materials has a corrugated microstructure, which significantly improves the bonding strength and overall performance of the material, including corrosion resistance and load-bearing capacity. Since the quality of this bonding interface is crucial to the overall performance of the material, a technology that can accurately detect its microstructure is needed. Ultrasonic scanning microscopy, as a non-destructive testing technology, uses high-frequency ultrasound to deeply detect the inside of the material and can provide high-resolution internal structure images. This technology can capture the details of the corrugated bonding interface, which is difficult to achieve with optical microscopy and X-ray detection. Ultrasonic scanning microscopy has shown its unique advantages in detecting the bonding interface of titanium / steel composite materials and can provide more accurate and safe detection results. Therefore, the present invention uses an ultrasonic scanning microscope to detect titanium / steel composite materials. First, start the ultrasonic scanning microscope and position the probe just above the center of the material to be tested. Select the detection parameters according to the sample thickness, including probe frequency, step, gain, and focus depth. Obtain B and C scan images to obtain the microstructure of the bonding interface. Finally, select the wave height and corrugation width indicators to characterize the microstructure.

[0035] Specifically, the process of the present invention is as follows:

[0036] Step 1. Move the probe of the ultrasonic scanning microscope to a position just above the center of the titanium / steel composite material sample;

[0037] Step 2. Setting the detection parameters of the ultrasonic scanning microscope according to the thickness of the sample;

[0038] Step 3. The ultrasonic scanning microscope scans and detects the sample to obtain an image of the sample;

[0039] Step 4. Analyze the image, obtain indicators about the sample, and characterize the sample.

[0040] Furthermore, the step 1 is specifically as follows: start the ultrasonic scanning microscope device. After the device is turned on, ensure that the probe is located directly above the center of the titanium / steel composite material. The key to this step is to accurately position the probe to ensure that the subsequent ultrasonic signal can be irradiated and received from the desired position, thereby obtaining accurate image data.

[0041] Furthermore, the step 2 is specifically as follows: according to the thickness of the sample, the detection parameters of the ultrasonic scanning microscope are adjusted. These parameters include the probe frequency, that is, the frequency setting of the ultrasonic wave, which is selected according to the thickness of the material sample and the required resolution. The step determines the interval or step length of the ultrasonic probe moving during the scanning process. The gain controls the signal strength received by the ultrasonic scanning microscope to optimize the contrast and clarity of the image. The focus depth is set at the composite material bonding interface position to ensure that a clear image is obtained within a specific depth range. The precise adjustment of these parameters is to ensure that high-quality and accurate ultrasonic microscopic image data is obtained during the detection process.

[0042] Furthermore, the step three is specifically as follows: after the scanning is completed, B and C scanning images are obtained by ultrasonic scanning microscope equipment to obtain the microstructure of the titanium / steel composite material bonding interface. The B scanning image is a cross-sectional image along the vertical direction of the sample, which can display the depth information of the titanium / steel composite material sample and the layered structure of the interface. The C scanning image is a top-view image of the sample, showing the characteristics of the material sample bonding interface. These different types of scanning images obtained by ultrasonic scanning microscope equipment can fully understand the microstructure and structural characteristics of the composite material bonding interface, and provide necessary data support for subsequent analysis and evaluation.

[0043] Furthermore, the step four is specifically as follows: after obtaining the scanning image, select indicators for characterizing the microstructure of the bonding interface of the composite material sample. The B-scan image is a cross-sectional image along the vertical direction of the sample, which can display the wave height of the titanium / steel composite material sample. The wave height refers to the vertical distance between the crest and the trough on the bonding interface. The C-scan image is a top-view image of the sample, which can display the corrugation width of the material sample. The corrugation width refers to the horizontal distance between two adjacent crests (or troughs) on the interface. These characterization indicators can quantify the geometric characteristics and morphology of the interface microstructure. By analyzing these indicators, the key characteristics of the bonding interface, such as corrugation consistency and bonding strength, can be evaluated, providing a scientific basis for further optimization of material properties.

[0044] The following is described using specific embodiments:

[0045] Embodiment 1:

[0046] A method for detecting and characterizing the microstructure of a titanium / steel composite material, the method achieves accurate detection of the bonding interface of the titanium / steel composite material by coordinated adjustment of multiple parameters of an ultrasonic scanning microscope device, including probe frequency, step, gain, and focus depth. Start the ultrasonic scanning microscope and accurately position the probe just above the center of the titanium / steel composite material sample. Select appropriate detection parameters according to the thickness of the sample, including probe frequency, step, gain, and focus depth. Obtain the microstructure of the bonding interface by acquiring B and C scan images. Select characterization indicators, such as wave height and corrugation width, to characterize the microstructure.

[0047] The method mainly comprises the following steps:

[0048] Step 1, positioning the probe: After starting the ultrasonic scanning microscope equipment, first make sure that the equipment is in normal working condition. Next, move the probe to a position directly above the center of the titanium / steel composite sample. This step is critical because accurate positioning of the probe is the basis for ensuring detection accuracy. By accurately aligning the probe, the ultrasonic signal can be vertically irradiated at the target position of the titanium / steel composite sample and reflected back from that position to receive, thereby obtaining high-quality image data.

[0049] Step 2, set the detection parameters: according to the thickness of the sample, adjust the various detection parameters of the ultrasonic scanning microscope. These parameters include the probe frequency, that is, the frequency setting of the ultrasonic wave, which is selected according to the thickness of the titanium / steel composite material sample and the required resolution. The step determines the interval or step length of the ultrasonic probe movement during the scanning process. The focus depth is set at the interface of the titanium / steel composite material sample to ensure that a clear image is obtained within a specific depth range. The gain control adjusts the received signal strength to optimize the contrast and clarity of the image. Figure 2 The figure shows a schematic diagram of the bonding interface of a titanium / steel composite material sample, wherein the sample includes a titanium layer 1 of a titanium / steel composite material, a steel layer 2 of a titanium / steel composite material, a titanium / steel composite material bonding interface ripple 3 between the titanium layer 1 and the steel layer 2, and a distance 4 from the titanium / steel composite material bonding interface to the material surface, which is used to determine the microscope focus depth and the titanium / steel composite material thickness 5. In this embodiment, the thickness of the titanium / steel composite material sample is 10 mm, and the height of the material bonding interface from the surface is 2 mm; the ultrasonic probe frequency is selected to be 50 MHz, the step is selected to be 10 μm, the focus depth is set to 2 mm, the focus is on the titanium / steel composite material bonding interface, and the gain is set to 20 dB.

[0050] Step 3: Obtain the test image: Obtain the B and C scan images by scanning with an ultrasonic scanning microscope to present the microstructure of the composite material interface. Figure 1As shown in FIG, the probe is moved along the X-axis direction of the sample to obtain the ultrasonic reflection signal inside the sample on the cross section and generate a B-scan image of the two-dimensional cross section. Figure 1 As shown, the probe is scanned on a two-dimensional plane formed by the X and Y axis directions of the sample, and the ultrasonic reflection signal within the focus area is intercepted to generate a C-scan image of the two-dimensional plane. Figure 3 As shown in the figure, it is a B-scan image of the composite material. The B-scan image can clearly observe the two-dimensional cross-section of the sample, and then according to the scale length in the image, the wave height in the image can be measured as an important indicator of interface consistency. Figure 4 The figure shows the C-scan image of the composite material sample. The C-scan image can clearly observe the overall two-dimensional plane of the sample, and then according to the ruler length in the image, the ripple width in the image is measured to reach 447um, which is an important indicator of interface uniformity and integrity. These different types of scanning images, B-scan images and C-scan images, combined together, can fully understand the microstructure and structural characteristics of the composite material interface, providing necessary data support for subsequent analysis and evaluation.

[0051] Step 4, analyzing indicators to characterize the structure: After obtaining the scanned image, select indicators used to characterize the microstructure of the composite interface, such as wave height and corrugation width. Wave height refers to the vertical distance between the peak and the trough on the bonding interface. Corrugation width refers to the horizontal distance between two adjacent peaks (or troughs) on the interface. By analyzing these indicators, the key characteristics of the composite material bonding interface, such as corrugation consistency and bonding, can be accurately evaluated, providing a scientific basis for further optimizing material performance. In this embodiment, Figure 3 The corrugated structure inside the titanium / steel composite material can be clearly observed. These corrugations are evenly distributed, the shapes of the crests and troughs are clearly discernible, and the wave height reaches 964um. Through a detailed analysis of these corrugated features, it can be concluded that the corrugation consistency of the material is good, which shows that the material maintains a high degree of consistency and stability during the manufacturing process. This consistency is crucial to the mechanical properties and durability of the material because it ensures uniform stress distribution in different areas of the material, thereby improving the reliability of the overall structure. In addition, good corrugation consistency also helps to improve the fatigue resistance of the material and extend its service life. Therefore, the corrugated features of the titanium / steel composite material measured by ultrasonic scanning microscopy not only show the microstructure of the material bonding interface, but also reflect the potential advantages of titanium / steel composite materials in practical applications.

[0052] The above description shows and describes several preferred embodiments of the present application, but as mentioned above, it should be understood that the present application is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not deviate from the spirit and scope of the present application, and should be within the scope of protection of the claims attached to the present application.

Claims

1. A method for detecting and characterizing the microstructure of a titanium / steel composite material, characterized in that: The method comprises the steps of: S1. Move the probe of the ultrasonic scanning microscope to a position just above the center of the titanium / steel composite sample; S2. According to the thickness of the sample, setting the detection parameters of the ultrasonic scanning microscope; S3. The ultrasonic scanning microscope scans and detects the sample to obtain an image of the sample; S4. Analyze the image, obtain indicators about the sample, and characterize the sample.

2. The method according to claim 1, characterized in that: The titanium / steel composite material comprises a titanium layer of the titanium / steel composite material, a steel layer of the titanium / steel composite material and a titanium / steel composite material bonding interface corrugation located therebetween.

3. The method according to claim 1, characterized in that: The thickness of the titanium / steel composite material is 10 mm.

4. The method according to claim 1, characterized in that The detection parameters include probe frequency, step, gain and focus depth.

5. The method according to claim 4, characterized in that The probe frequency is 50 MHz, the step is 10 μm, the gain is 20 dB, and the focus depth is 2 mm.

6. The method according to claim 2, characterized in that The images include a two-dimensional cross-sectional XOZ image and a two-dimensional planar XOY image.

7. The method according to claim 6, characterized in that The two-dimensional cross-sectional XOZ image is used to measure the height of the corrugations in the image, and the two-dimensional planar XOY image is used to measure the width of the corrugations in the image.

8. A titanium / steel composite material microstructure detection and characterization system, characterized in that: The system is used to implement the method described in any one of claims 1 to 7, and the system includes: A positioning module, used for positioning the probe of the ultrasonic scanning microscope and the position of the titanium / steel composite material sample; A setting module, used for setting the detection parameters of the ultrasonic scanning microscope according to the thickness of the sample; An acquisition module, used for the ultrasonic scanning microscope to scan and detect the sample to obtain an image of the sample; The analysis and characterization module is used to analyze the image to obtain an index characterization of the sample.

9. A computer device, characterized in that: The computer device comprises a processor and a memory, wherein a computer program is stored in the memory, and the computer program is loaded and executed by the processor to implement the method according to any one of claims 1 to 7.

10. A computer-readable storage medium, characterized in that: The computer-readable storage medium stores a computer program, which is loaded and executed by a processor to implement the method according to any one of claims 1 to 7.